1989
DOI: 10.1093/jac/24.4.485
|View full text |Cite
|
Sign up to set email alerts
|

The molecular basis of the inhibitory activities of type A and type B synergimycins and related antibiotics on ribosomes

Abstract: Synergimycins A and B act synergistically in vivo; the mixture of the two compounds is more powerful than the individual components and their combined action is irreversible. Type A (virginiamycin M, VM-like) components inactivate the donor and acceptor sites of peptidyltransferase, thus interfering with the corresponding functions of the enzyme. They block two of the peptide chain elongation steps: aminoacyl-tRNA (AA-tRNA) binding to the A site of ribosomes, and peptide bond formation with peptidyl-tRNA (pep-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
31
0
2

Year Published

1999
1999
2013
2013

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(33 citation statements)
references
References 0 publications
0
31
0
2
Order By: Relevance
“…The dependence of the yield of the PIA-dependent rRNA modification on time of irradiation, PIA concentration, and wavelength of the UV light+ A,B: Time dependence: Complexes of 70S (0+15 mM) ribosomes and PIA (10 mM) were irradiated at 365 nm for the time (minutes) indicated below the gel+ rRNA was isolated as described in Materials and Methods and analyzed by extension from primer EC2621+ The yield of PIA-dependent modification at m 2 A2503/⌿2504 was quantified relative to the natural stop at A2497 using an Instant Imager and plotted as a function of time+ C,D: PIA concentration dependence: Complexes of 50S subunits (50 nM) and increasing amounts of PIA were irradiated at 365 nm for 20 min and treated further as described above+ The concentration of PIA (in mM) is indicated below the gel+ The yield of modification at m 2 A2503/⌿2504 was quantified relative to the natural stop at A2497 using an Instant Imager and plotted as a function of the concentration of PIA+ E: Wavelength dependence: 50S subunits (0+15 mM) were irradiated for 20 min in the presence (Ï©) and absence (ÏȘ) of PIA (10 mM) at 254 nm, 312 nm, or 365 nm+ When indicated (Ï©), a petri dish was used as a filter (,300 nm)+ G, A, U, and C represent nucleotide sequencing tracks+ Inhibition by the three macrolides (Fig+ 5A,B) probably results from direct competition because they are likely to occupy physically overlapping binding sites (Di Giambattista et al+, 1987)+ Unlike the effects observed for the other drugs, the presence of the stops at A2062, for samples containing tylosin and spiramycin (Fig+ 5B), was independent of the presence of PIA (data not shown) and we are currently investigating the nature of these effects+ Chloramphenicol produced the most dramatic effects by blocking the modification at m 2 A2503/ ⌿2504 (Fig+ 5A) and producing a shift in the primerextension stops from G2061/A2062 to A2062/C2063 (Fig+ 5B)+ Since chloramphenicol, like the streptogramin A drugs, binds to the ribosome in the presence of PIA (de Bethune & Nierhaus, 1978;Di Giambattista et al+, 1989), the results strongly suggest that it also alters the conformation of the peptidyl transferase loop, which is consistent with the complex rRNA footprints produced by these drugs (Fig+ 2C;Moazed & Noller, 1987;Rodriguez-Fonseca et al+, 1995;Porse & Garrett, 1999)+…”
Section: Interference By Other Peptidyl Transferase Antibioticsmentioning
confidence: 98%
See 1 more Smart Citation
“…The dependence of the yield of the PIA-dependent rRNA modification on time of irradiation, PIA concentration, and wavelength of the UV light+ A,B: Time dependence: Complexes of 70S (0+15 mM) ribosomes and PIA (10 mM) were irradiated at 365 nm for the time (minutes) indicated below the gel+ rRNA was isolated as described in Materials and Methods and analyzed by extension from primer EC2621+ The yield of PIA-dependent modification at m 2 A2503/⌿2504 was quantified relative to the natural stop at A2497 using an Instant Imager and plotted as a function of time+ C,D: PIA concentration dependence: Complexes of 50S subunits (50 nM) and increasing amounts of PIA were irradiated at 365 nm for 20 min and treated further as described above+ The concentration of PIA (in mM) is indicated below the gel+ The yield of modification at m 2 A2503/⌿2504 was quantified relative to the natural stop at A2497 using an Instant Imager and plotted as a function of the concentration of PIA+ E: Wavelength dependence: 50S subunits (0+15 mM) were irradiated for 20 min in the presence (Ï©) and absence (ÏȘ) of PIA (10 mM) at 254 nm, 312 nm, or 365 nm+ When indicated (Ï©), a petri dish was used as a filter (,300 nm)+ G, A, U, and C represent nucleotide sequencing tracks+ Inhibition by the three macrolides (Fig+ 5A,B) probably results from direct competition because they are likely to occupy physically overlapping binding sites (Di Giambattista et al+, 1987)+ Unlike the effects observed for the other drugs, the presence of the stops at A2062, for samples containing tylosin and spiramycin (Fig+ 5B), was independent of the presence of PIA (data not shown) and we are currently investigating the nature of these effects+ Chloramphenicol produced the most dramatic effects by blocking the modification at m 2 A2503/ ⌿2504 (Fig+ 5A) and producing a shift in the primerextension stops from G2061/A2062 to A2062/C2063 (Fig+ 5B)+ Since chloramphenicol, like the streptogramin A drugs, binds to the ribosome in the presence of PIA (de Bethune & Nierhaus, 1978;Di Giambattista et al+, 1989), the results strongly suggest that it also alters the conformation of the peptidyl transferase loop, which is consistent with the complex rRNA footprints produced by these drugs (Fig+ 2C;Moazed & Noller, 1987;Rodriguez-Fonseca et al+, 1995;Porse & Garrett, 1999)+…”
Section: Interference By Other Peptidyl Transferase Antibioticsmentioning
confidence: 98%
“…Antibiotics are important tools for the treatment of many serious human and animal infections+ However, the increasing use and misuse of these drugs in both the health care and agricultural sectors have led to increasing problems with drug-resistant bacteria, with severe consequences for human health+ One group of such therapeutically important antibiotics are the streptogramins, which contain A and B components and target the peptidyl transferase center of the large ribosomal subunit, where they inhibit peptide elongation+ Resistance to both streptogramin components is widespread in diverse bacterial communities+ Streptogramins inhibit peptide elongation by a mechanism that is only partially understood+ Moreover, the two components act synergistically such that although the individual A and B components are bacteriostactic, together they can be bacteriocidal (Gale et al+, 1981;Di Giambattista et al+, 1989)+ The observation that neither streptogramin component affects protein synthesis on polysomes suggests that they act during the initial rounds of protein synthesis in vivo (Contreras & VĂĄzquez, 1977)+ In contrast to the A component, streptogramin B has no direct effect on peptide bond formation with puromycin, in vitro, a property which it shares with the smaller macrolides+ Streptogramin B and these macrolides also share a similar resistance mechanism associated with either N-6 methylation (MLS B phenotype), or mutation, at A2058 within the peptidyl transferase loop of 23S rRNA that is important for peptide bond formation (Cundliffe, 1990;Garrett & RodriguezFonseca, 1995)+ The binding sites of both streptogramin components have been assigned indirectly to nucleotides within the peptidyl transferase loop of 23S rRNA on the basis of chemical footprinting and mutational analyses (Vanuffel et al+, 1992;Rodriguez-Fonseca et al+, 1995;Porse & Garrett, 1999) and, for the B component, to the vicinity of ribosomal proteins L18 and L22 by affinity labeling (Di Giambattista et al+, 1990)+ However, although several lines of evidence suggest that these and other peptidyl transferase drugs interact with rRNA, no direct binding to isolated 23S rRNA has been detected for any of them (reviewed by Kirillov et al+, 1997)+ In the present work, we provide evidence for both a direct interaction of the streptogramin B drug, pristinamycin IA (PIA; Fig+ 1), with highly conserved nucleotides of the peptidyl transferase loop of 23S rRNA and for two PIA-dependent modifications in the same functional rRNA region+ Moreover, we demonstrate that the presence of pristinamycin IIA (PIIA, a streptogramin A), chloramphenicol, carbomycin, tylosin, spiramycin and P-site-bound tRNA alter the PIA-induced effects+ Finally, evidence is provided for the binding of PIA to protein-free mature rRNA, and to small rRNA fragments excised from the peptidyl transferase loop region, which is dependent on at least one posttranscriptional modification+…”
Section: Introductionmentioning
confidence: 99%
“…This increase in antibacterial efficacy has been shown to originate from synergistic binding of the type A and type B streptogramins to distinct sites on the ribosome (35,36). Thus, binding of streptogramin A antibiotics to the ribosome increases the affinity of streptogramin B antibiotics for the ribosome by up to 40-fold, rendering dual antibiotic binding essentially irreversible (37). The binding of the type A antibiotics is thought to change the conformation of the ribosomal RNA to expose a high-affinity binding site for the type B compounds (37).…”
mentioning
confidence: 99%
“…Thus, binding of streptogramin A antibiotics to the ribosome increases the affinity of streptogramin B antibiotics for the ribosome by up to 40-fold, rendering dual antibiotic binding essentially irreversible (37). The binding of the type A antibiotics is thought to change the conformation of the ribosomal RNA to expose a high-affinity binding site for the type B compounds (37). The synergistic antibiotic effect of the streptogramins has been exploited clinically in the form of a combination of semisynthetic pristinamycin IA and IIA derivatives known as synercid, which is used for the treatment of multidrug-resistant bacterial infections.…”
mentioning
confidence: 99%
“…These drugs block protein translation by binding to the P-site of the ribosome (type A streptogramin) and by occluding the entrance to the peptide exit tunnel (type B streptogramin). Binding of the type A streptogramin results in a conformational change in the ribosome that facilitates binding of the type B streptogramin (3)(4)(5). It is this inhibitor-induced conformational change that forms the molecular basis of the synergistic antimicrobial activity that is the hallmark of this class of antibiotics.…”
mentioning
confidence: 99%